Efektivitas Penggunaan Integrated Library System (Inlislite) Dinas Kearsipan Dan Perpustakaan Provinsi Sumatera Barat Menggunakan Human Organization Technology (HOT) Fit Model - Puji Mori; Gustina Erlianti (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The aim of this research is to describe the effectiveness of using INLISLite for the West Sumatra Province Archives and Library Service using the Human Organization Technology (HOT) Fit Model. This research is quantitative research with descriptive methods. The population in this study were librarians who used INLISLite while on duty at the West Sumatra Province Archives and Library Service, totaling 13 librarians with sampling using a saturated sampling technique. The main instrument used is a research questionnaire which has been tested for validity and reliability. Data collection was carried out by distributing questionnaires. Data were analyzed through inspection and tabulation stages. The research results are: First, the Human Indicator obtained an average value of 2.60 which is on an interval scale of 2.50 - 3.24 so it is included in the good category. Second, the Organizational Indicator (Organization) obtained an average of 3.16 which is on an interval scale of 2.50 - 3.24 so it is included in the good category. Third, the Technology Indicator (Technology) obtained an average of 3.21 which is on an interval scale of 2.50 - 3.24 so it is included in the good category. Based on the results of this research, it can be concluded that the Effectiveness of Using INLISLite using the HOT Fit Model obtained an average of 2.99. This score is in the interval 2.50 - 3.24 so it is included in the good category.